2018
DOI: 10.1038/s41545-018-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Artificial water channels—deconvolution of natural Aquaporins through synthetic design

Abstract: Artificial Water Channels (AWCs) have been developed during the last decade with the hope to construct artificial analogues of Aquaporin (AQP) proteins. Their osmotic water permeability are in the range of natural transporters, making them suitable candidates that can potentially transport water at lower energy and operating cost. Compared to AQPs, AWCs would have several potential advantages, such as improved stability, simple and scalable fabrication and higher functional density when confined in 2D membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…Bioinspired synthetic water channels commonly have water permeable central apertures surrounded by hydrophobic outer shells for stabilizing within the hydrophobic core of lipid bilayer systems 14 . The two general synthetic strategies are unimolecular tubular architectures 5 9 , 13 and bottom-up assemblies 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Bioinspired synthetic water channels commonly have water permeable central apertures surrounded by hydrophobic outer shells for stabilizing within the hydrophobic core of lipid bilayer systems 14 . The two general synthetic strategies are unimolecular tubular architectures 5 9 , 13 and bottom-up assemblies 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In the application of AQP biological membranes, main challenges might include: i) difficulty in controlling stable structure and scaling-up because of insufficient stability of AQP proteins in high saline and operational pressure; ii) fragile lipid bilayers show poor compatibility with the practical applications; iii) high fabrication cost compared with synthetic counterparts [11,12] . Therefore, researchers attempt to mimic the structure of AQP [13] and synthesize artificial simpler molecules with similar structural and thus water transport properties, namely artificial water channels, first reported by Barboiu et al [14] Common artificial water channels such as carbon nanotubes [15][16][17] (CNTs), imidazole-quartet water channel [14,18,19] (IQWC) and peptide-appended pillar [5]arene [20][21][22] (PAP) have been explored during the last decades. Noy et al [17] indicated that water permeability in 0.8-nanometer-diameter CNTs, which confined water down to a single-file chain, exceeded that AQP.…”
Section: Introductionmentioning
confidence: 99%
“…This was the reason synthetic alternatives were sought for. The synthetic structures serving a function analogous to natural aquaporins are called artificial water channels [152,153].…”
Section: Artificial Water Channelsmentioning
confidence: 99%